Positive Youth Development in Croatia: School and Family Factors Associated With Mental Health of Croatian Adolescents - Novak, Miranda; Parr, Nicholas J.; Ferić, Martina; Mihić, Josipa; Kranželić, Valentina (Frontiers in Psychology, 2021)
Introduction A framework for understanding the interrelationship of individual and environmental factors that influence adolescent health and wellbeing, as well as opportunities for policy-level interventions, is known as Positive Youth Development. The current study represents one of the largest studies of Croatian adolescents to date, and aimed to examine associations between school and family factors linked to positive youth development, and mental health outcomes experienced by Croatian youth. Methods A multi-site survey study was conducted among adolescents (N = 9,655) residing in the five most populous cities in Croatia, with the aim of examining cross-sectional associations of family and school factors with adolescent mental health. The mean age of participants was 16.3 years (SD = 1.2), and 52.5% were female. School and family factors included school attachment, school commitment, family communication and family satisfaction. Depression, anxiety and stress were assessed as outcomes. Multigroup structural equation modeling was used to examine relations of interest among female and male adolescents. Results Among school factors, increased school attachment was found to be significantly associated with reduced depression, anxiety and stress for female adolescents, and with decreased depression and stress for male adolescents. Increased school commitment was significantly associated with decreased depression and anxiety for female adolescents, and with reduced anxiety and stress among male adolescents. Conversely to female adolescents, an increase in school commitment was associated with an increase in anxiety and stress for male adolescents. Increases in family communication were significantly associated with reduced depression, anxiety and stress only for male adolescents, while increased family satisfaction was significantly associated with reduced depression, anxiety and stress for female adolescents and with decreased depression and stress for male adolescents. Conclusions Findings suggest that interventions for mental health promotion and prevention of internalizing problems should address both school and family contexts, and may be more effective when accounting for differing developmental experiences of female and male adolescents.